Application of Distributed Fiber Temperature Detection Technology in the Shaft Freezing Restoration Project - Zheng Xiao Liang; Hu Ye-lin; Shen Hua-jun; Xie Hong-zhi; Dou An-feng; Yu Jin-chang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
According to the particularity of the restoration project of using freezing method to conduct shaft-forming well wall, the monitoring of the conventional hydrological hole and thermometer hole, new means of detection are added, and distributed fiber temperature detection technology is used to check the temperature of each longitudinal freezer. The principle, composition, detection method and temperature measuring optical cable structure of the distributed fiber temperature detection system are introduced in detail. Field measured data is given, which has large data size and can reflect the actual development status of freezing wall comprehensively and intuitively compared with the traditional thermometer hole data. Data analysis provides the basis for guiding the freeze construction being carried out safely and smoothly. The structure of system is simple and flexible, and the detection method has a certain promotional value. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4436